The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1017/s0025315414000356
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive traits and seasonal variability ofMerluccius merlucciusfrom the Tunisian coast

Abstract: Merluccius merlucciusis an economically and ecologically important demersal species inhabiting the Atlantic Ocean and the Mediterranean Sea; however, reproductive knowledge about this species, along the North African coast is still missing. Monthly samples were collected from November 2010 to October 2011 along the North Tunisian coast. Morphometric parameters were measured, and histological preparations of gonadic tissues provided detailed information on the reproductive biology. Ovary maturity data showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 57 publications
(87 reference statements)
0
7
1
Order By: Relevance
“…Recasens et al, (2008) reported the L50 value as 35.8 cm in the western Mediterranean. Moreover, the values reported in this study are higher than those reported for the Tunisian coast (Khoufi et al, 2014), and lower than those reported for Iberian Atlantic waters (Piñeiro and Saínza, 2003) and the Gulf of Lions (Mellon-Duval et al, 2009). These differences may be explained by the phenotypical response to some environmental changes or by the evolutionary consequence of some selective pressures such as fishery efforts (Barot et al, 2004).…”
Section: Total Lengthcontrasting
confidence: 79%
“…Recasens et al, (2008) reported the L50 value as 35.8 cm in the western Mediterranean. Moreover, the values reported in this study are higher than those reported for the Tunisian coast (Khoufi et al, 2014), and lower than those reported for Iberian Atlantic waters (Piñeiro and Saínza, 2003) and the Gulf of Lions (Mellon-Duval et al, 2009). These differences may be explained by the phenotypical response to some environmental changes or by the evolutionary consequence of some selective pressures such as fishery efforts (Barot et al, 2004).…”
Section: Total Lengthcontrasting
confidence: 79%
“…Even though macroscopic analysis is not satisfactory for distinguishing between immature, maturing and resting females (Murua et al , 2003; Vitale et al , 2006; Domínguez-Petit, 2007; Recasens et al , 2008; Ferreri et al , 2009), Khoufi et al (2014) stated a good correspondence of immature females between macroscopic and histological reproductive phase identification, confirming the skill of the operators. Although we did not perform histological reproductive analysis in our study, our results concerning GSI values are similar with those of Khoufi et al (2014), both indicating a protracted spawning season throughout the year peaking in April. Moreover, previous histological investigation of ovaries showed that European hake exhibits indeterminate fecundity and spawns year-round with peak spawning occurring in January–March (Murua & Motos, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Growth of European hake is included in many scientific papers (Alegria & Jukic, 1990; Erzini, 1991; Campillo, 1992; Abella et al , 1995; Aldebert & Recasens, 1995; Alemany & Oliver, 1995; D'Onghia et al , 1995; Stergiou et al , 1997; Bouaziz et al , 1998; Uçkun et al , 2000; Zoubi, 2001; Garcia-Rodriquez & Esteban, 2002; Pineiro & Sainza, 2003; Randall, 2003; Mellon-Duval et al , 2010). Reproduction of the species was a focus of many researchers (Cohen et al , 1990; Muus & Nielsen, 1999; Akalın, 2004; Murua & Motos, 2006; Khoufi et al , 2014). Feeding habits of European hake were reported by Carpentieri et al (2005), Cartes et al (2009) and Philips (2012).…”
Section: Introductionmentioning
confidence: 99%
“…In multiple-spawning fishes, specifically those with asynchronous gonadic development, such as sardine, macroscopic determination of spawning phase is difficult without the support of microscopic examination; this is due to its subjectivity and variability, which represent a source of bias particularly relevant in discriminating immature from mature individuals (Costa, 2009;Ferreri et al, 2009;Khoufi et al, 2014). Nonetheless, macroscopic evaluation of gonads is widely adopted in the fishery resources assessment, because it allows examining a wider number of fishes (Ferreri et al, 2009;Basilone et al, 2015).…”
Section: Discussionmentioning
confidence: 99%